ANALISIS PENILAIAN KESEHATAN KOPERASI SIMPAN PINJAM BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTERIAN KOPERASI USAHA KECIL DAN MENENGAH No: 14/Per/DEP.6/IV/2016 PADA KOPERASI PEGAWAI KEJAKSAAN TINGGI SUMATERA SELATAN - Ariansyah, Imam; Nurmala, Nurmala (Universitas Indo Global Mandiri Palembang, 2019)
This study aims to assess the health level of savings and loan cooperatives based on regulations of the superintendent of the ministry of cooperatives of small and medium enterprises No, 14 / per / DEP.6 /IV/2016 Padakoperasi high prosecutor's office in South Sumatra. The population in this study is a cooperative financial report, while the sample is the 2016-2018 period financial statement. Discussion of Research Results The Capital Value is obtained a score of 7.1 the average score of 1.50 the highest score with susceptible standards ≤ 51. get Predicate in Special Supervision. The Product Quality Asset Quality score is scored 10 with an average score of 10 with a score the highest 100 with vulnerable 80 ≤ X ≤ 100. Get a healthy predicate. Efficiency aspect obtained an average score of 3.33.% Of the maximum score of 4, the highest score of 100, with a range of 80 ≤ X ≤ 100. Got a healthy predicate, Liquidity Aspect obtained a score of 2.5 with a value of 25 Maximum score of 100, with a standard range rentang 51.00. Obtaining a Predicate under Special supervision, the Aspects of Independence and Growth obtained an average of 2.25 maximum score of 3 in the range of 66 ≤ X ≤ 80. Self-Aspect score = average 7 with a maximum score of 7 where the ratio is obtained with a standard range of 80 ≤ X ≤ 100. Get healthy predicate.Keywords: Capital Aspect, earning assets, efficiency, liquidity, independence and growth, identity